ROLE OF TRANSCRANIAL ULTRASOUNDIN HOSPITALISED HIGH-RISK NEWBORNS : A PROSPECTIVE OBSERVATIONAL STUDY - Narayan prasad Modi; Tejawsini Jami; Narayan prasad Modi; MANGAL CHARAN MURMU MANGAL (Student's Journal of Health Research, 2023)
Introduction: High-risk neonates are always an increased risk of morbidity and mortality. They contribute to as high as 15% of all morbidities and mortalities in newborns independently. Hence identifying them early and appropriate management of these high-risk newborns is important. Cranial ultrasonography (CUS) is a reliable tool for detecting congenital and acquired abnormalities of the perinatal brain and the most frequent patterns of brain injury in preterm and full-term neonate. Aim& Objective: To study cranial ultrasound findings in high-risk neonates and to correlate the clinical manifestations with cranial ultrasonogram findings. Material& Method: This study was a prospective observational study carried out at Department of Paediatrics, SVPPGIP & SCBMCH between October 2019 to October 2021. Observation: The incidence of CUS abnormalities in high-risk neonates in the present study was 54.5%.  There was a statistically significant correlation between birth asphyxia and abnormal CUSfindings(p<0.001), birth trauma and abnormal CUS findings(p<0.001), hypoglycemia and abnormal CUS findings(p=0.004), and abnormal Central Nervous System examination and abnormal CUS findings(p=0.008). Conclusion: Cranial ultrasound is important and critical as an investigation modality and effectively documents morphology of brain damage. Recommendation : The concept of 'survival' of the newborn has given way to the importance of 'intact survival' of the high-risk infant, prompting the initiation of strategies to identify neurological sub-normality at the earliest. CUS is an ideal tool for the primary screening of the neonatal brain, it must be done in all high-risk neonates for prognosticate and guide to outcome.